Artificial intelligence and 3D printing technology in orthodontics: future and scope - Mahamad Irfanulla Khan; Laxmikanth SM; Tarika Gopal; Praveen Kumar Neela (AIMS Biophysics, 2022)
New digital technologies, like in other fields, have revolutionized the health care field and orthodontic practice in the 21st century. They can assist the health care professionals in working more efficiently by saving time and improving patient care. Recent advances in artificial intelligence (AI) and 3D printing technology are useful for improving diagnosis and treatment planning, creating algorithms and manufacturing customized orthodontic appliances. AI accomplishes the task of human beings with the help of machines and technology. In orthodontics, AI-based models have been used for diagnosis, treatment planning, clinical decision-making and prognosis prediction. It minimizes the required workforce and speeds up the diagnosis and treatment procedure. In addition, the 3D printing technology is used to fabricate study models, clear aligner models, surgical guides for inserting mini-implants, clear aligners, lingual appliances, wires components for removable appliances and occlusal splints. This paper is a review of the future and scope of AI and 3D printing technology in orthodontics.